Analysis and measurement of the impact of exchange rate changes and their repercussions on local investment in Iraq for the period (2004-2022) - Dr. Faten Saeed Hameed (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The research is concerned with analyzing and measuring the impact of exchange ratechanges and their repercussions on local investment in Iraq during the period (2004-2022), asthe relationship between them is affected by global economic conditions such as high or lowoil prices and demand for the exchange rate internationally, as the response of the investmentsectors in Iraq to changes in the exchange rate varies, as the decline in the exchange rateencourages investment in the export sector and proves investments in the import-dependentsector, unlike its rise, which negatively affects the local economy The authorities are workingto take some measures and procedures such as providing financial support and incentives tosupport projects and thus promote local investment, as well as the political and securityfluctuations in Iraq that affect investor confidence and investment decisions and thus affecteconomic stability, and the relationship between local investment in Iraq and exchange ratechanges is somewhat complicated as they are affected by each other, so the monetaryauthority and investors must understand this relationship and understand its strategies in away that enhances and supports the investment climate in the Iraqi economy, Domesticinvestment and the exchange rate significantly affect the economic relations described in theARDL model , so it is recommended to develop fiscal and monetary economic policies thatsupport domestic investments and improve exchange rate stability to achieve moresustainable economic results.